1977
DOI: 10.1084/jem.145.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility antigen-activated cytotoxic T lymphocytes. II. Estimates of the frequency and specificity of precursors.

Abstract: Using limiting dilutions of responding cells in mouse mixed leukocyte cultures, we obtained direct estimates of the minimum frequency of precursors of cytotoxic T lymphocytes (CTL.P) for a variety of antigens. Depending on the strain combination, there were as many as 4-15 CTL.P reactive to DBA/2 among 10(4) lymph node cells. Taking into account that only 5-10% of peripheral T lymphocytes have the potential to develop into cytotoxic T lymphocytes (CTLs) (6), this implies that at least 1-2% of all CTL.P are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(106 citation statements)
references
References 31 publications
(32 reference statements)
9
95
2
Order By: Relevance
“…The results shown are also in agreement with those of others which have shown that there is a higher CTL-P frequency for an MHC plus a non-MHC alloantigenic difference than for MHC alloantigens alone (Lindahl and Wilson, 1977).…”
Section: The Frequency Of Ctl-p Reactive To Taa and Mhc Alloantigenssupporting
confidence: 82%
See 1 more Smart Citation
“…The results shown are also in agreement with those of others which have shown that there is a higher CTL-P frequency for an MHC plus a non-MHC alloantigenic difference than for MHC alloantigens alone (Lindahl and Wilson, 1977).…”
Section: The Frequency Of Ctl-p Reactive To Taa and Mhc Alloantigenssupporting
confidence: 82%
“…of the background for a particular target cell, and then scoring the wells assayed with that target positive if the counts in the supernatant were greater than the background count + 3 x S.D. of the background, as advocated by Lindahl and Wilson (1977). The percentage of negative wells for each responder number was then determined and plotted on a logarithmic scale against the responder number on an arithmetic scale, for analysis by Poisson distribution as described in detail previously (Burton et al, 1980).…”
Section: Determination Of the Frequency Of Ctl-p Reactive To Mhc Allomentioning
confidence: 99%
“…16,20 Accordingly, a fetal T cell to a given alloantigen when compared with individual autoantigens. 41 Our findings suggested a potential model for how tolerance could be achieved to antigens perceived by the fetal immune system in utero. 42 We and others showed that human fetal lymphoid tissues, and some non-lymphoid tissues, contained small but detectable levels of maternal cells.…”
Section: Mixed Chimerism and Immunological Tolerancementioning
confidence: 99%
“…Limiting dilution techniques have now been developed whieh permit an analysis ofthe various T lymphoeyte subsets (10)(11)(12)(13). Previous investigations using limit ing dilution techniques in miee have shown that iron: reduces the response by allospecifie eytotoxie T lymphoetyes (14,15); it reduces the ability of muritie CD8" T lymphoeyles to proliferate: it also reduces the proliferative response of human CD4 ^ memory T lymphoeytes to tetanus toxoid antigen (16).…”
Section: Introddcnonmentioning
confidence: 99%